1993
DOI: 10.1093/tropej/39.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, Immunity and Infections: T Lymphocyte Subpopulations in Protein--Energy Malnutrition

Abstract: Protein energy malnutrition (PEM) is one of the most frequent causes of secondary immune deficiency states. Alterations either in cellular or humoral immune mechanisms increase the susceptibility to infections in the malnourished organism. Infections aggravate the interrelationship of malnutrition to immune deficiency and infections, resulting in future adverse effects of malnutrition on humoral and cellular immune systems, IgG, IgM, IgA, C3, and T lymphocyte subpopulations were identified in 29 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…In 17 of 21 studies, levels of C3 were depressed in malnourished children [89] [94] [99] [106] [124]–[125] [127]–[130] [144]–[154]. Two studies found C3 to correlate with albumin [94] [148], and with one exception [94], C3 levels were lower in children with oedematous than non-oedematous malnutrition [89] [146] [149] [150]–[151] [153].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 17 of 21 studies, levels of C3 were depressed in malnourished children [89] [94] [99] [106] [124]–[125] [127]–[130] [144]–[154]. Two studies found C3 to correlate with albumin [94] [148], and with one exception [94], C3 levels were lower in children with oedematous than non-oedematous malnutrition [89] [146] [149] [150]–[151] [153].…”
Section: Resultsmentioning
confidence: 99%
“…Early studies identified T-lymphocytes as those forming rosettes with sheep red blood cells, while later studies used monoclonal antibodies to CD3. Using the rosette-method, 19 of 20 studies found lower levels of T-lymphocytes [28] [87] [93] [101] [128] [130] [144] [183] [186]–[187] [191] [199] [203]–[210]. Four studies using monoclonal CD3-antibodies and cell-counting by microscopy also found reduced levels of T-lymphocytes in malnourished children [144] [167][168] [207].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Last but not the least, malnutrition is the most common cause of immunodeficiency, and malnutrition in the uterus is one of the major causes of IUGR (Zijlstra et al, 1999;Özkan and Olgun, 1993). IUGR neonatal piglets might be good models of malnutrition research.…”
Section: Discussionmentioning
confidence: 99%